2011
DOI: 10.1371/journal.pone.0027590
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable Hexameric Form of Eis (Rv2416c) Protein of M. tuberculosis Plays an Important Role for Enhanced Intracellular Survival within Macrophages

Abstract: Eis protein is reported to enhance the intracellular survival of Mycobacterium tuberculosis in human macrophages. Eis protein is not only known to skew away the immunity by disturbing the protective TH1 response, but aminoglycoside acetyltransferase activity of Eis is reported to regulate autophagy, inflammation and cell death. Here we have gained insight into the structure-function properties of Eis. Eis protein is a hexameric αβ protein. Although urea and guanidinium hydrochloride (GdmCl) was found to induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…This result also indicates the delayed clearance of M. smegmatis harboring either RvErp or Rv2212. Similar results have also been reported earlier for Eis protein, a thermostable aminoglycoside acetyltransferase, which enhances the survival of Mycobacterium within macrophages (13,31). A recent report by Pedroza-Roldan et al (17) has also shown that the overexpression of Rv2212 caused the enhanced replication and survival of Mycobacterium bovis BCG Pasteur 1173P2.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This result also indicates the delayed clearance of M. smegmatis harboring either RvErp or Rv2212. Similar results have also been reported earlier for Eis protein, a thermostable aminoglycoside acetyltransferase, which enhances the survival of Mycobacterium within macrophages (13,31). A recent report by Pedroza-Roldan et al (17) has also shown that the overexpression of Rv2212 caused the enhanced replication and survival of Mycobacterium bovis BCG Pasteur 1173P2.…”
Section: Discussionsupporting
confidence: 85%
“…M. smegmatis transformed with vector alone was included in every experiment as a negative control. The intracellular survival assay was performed as described earlier (13).…”
Section: Methodsmentioning
confidence: 99%
“…(56) The escape mechanism is unknown, but efficient intracellular survival of Mt requires a strong thermodynamic stability of proteins. (57) We recently showed in vitro that isolated sub-hexameric assemblies of Mt-NDPK are inactive, complete assembly being essential for function. (53) By combining crystallography and biochemistry, we also demonstrated that hexamer's high thermostability (76°C) is dependent on six inter-subunit R80-D93 salt bridges.…”
Section: Figurementioning
confidence: 99%
“…An M. tuberculosis protein termed Eis (enhanced intracellular survival) (Shin et al 2010a;Ganaie et al 2011;Kim et al 2012b) may interact with specific autophagy factors or affect upstream signaling regulators. Eis is an 1-aminoacetyltransferase that acetylates Lys-55 in a JNK-specific phosphatase (Kim et al 2012b).…”
Section: Tuberculosis Possesses Countermeasures Against Autophagymentioning
confidence: 99%
“…Eis is an 1-aminoacetyltransferase that acetylates Lys-55 in a JNK-specific phosphatase (Kim et al 2012b). JNK action is important for activation of the key autophagy regulator Beclin 1, and thus Eis may modulate autophagy (Shin et al 2010a;Ganaie et al 2011;Kim et al 2012b). A mycobacterial glycolipid lipoarabinomannan has also been reported as inhibiting autophagy (Shui et al 2011).…”
Section: Tuberculosis Possesses Countermeasures Against Autophagymentioning
confidence: 99%